Niger : Report on the Observance of Standards and Codes-Data Module, Response by the Authorities, Detailed Assessments Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2006)
Niger's overall macroeconomic statistics is a picture of contrasts. Establishing the National Statistical Institute (INS) and giving it a clear and precise mandate is a step in the right direction. Accuracy and reliability suffer from the weakness of data sources, notably in national accounts and price statistics. Niger meets the General Data Dissemination System (GDDS) periodicity recommendations but falls below these recommendations for the timeliness of dissemination. The paper provides a summary of assessment by IMF staff and their recommendations.